(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Chronic obstructive pulmonary disease (COPD) often causes pneumothorax, a severe symptom. This symptom is common among COPD patients in Thai Binh General Hospital. This study aims to assess the treatment outcome of this disease. Methods: This was descriptive research conducted among 110 patients with COPD who had pneumothorax complications in Thai Binh General Hospital from 1/2019 to 12/2021. This research focused on age, gender, occupation, smoking history, hospitalizations for COPD, clinical symptoms, difficulty breathing status, air leakage on X-ray level, treatment method, duration of drain the pleural space, length in hospital and outcome treatment. Results: The result indicated that most of the sample was male (92.7%). The average age of 68.1 years, with 82.7% of patients more than 60 ages. Almost all the patients (95.5%) had a history of smoking. 100% of patients had lead two hospitalizations for COPD, with 11% recurrent pneumothorax. More than 72% of patients had symptoms of severe dyspnea and chest pain and 91.8% with large pneumothorax requiring intervention. 35.5% of patients had surgery and 2.7% had persistent air leakage. There was a significant difference in time to drain the pleural space between the surgical and non - surgical groups (4.4 compared to 6.3 days). The length in the hospital was 10.1 days in the surgical group compared to 7.3 days in the group without surgery. There were 80.9% of patients with good outcome treatment. Conclusion: Treatment of pneumothorax in patients with COPD at Thai Binh Provincial General Hospital has good results.